Failure-mode transition in resistance spot welded DP780 advanced high-strength steel - Abadi, Mehdi Mansouri Hasan (Materiali in tehnologije, 2014)
Resistance spot welds of advanced high-strength steels (AHSSs) exhibit a high tendency to fail in the interfacial failure mode (i.e., a failure through the fusion zone). It is also evident that the conventional recommendations (based on the sheet thickness) for weld sizing, ensuring the pullout failure mode of welds, are not dominant in AHSS welds. Therefore, there is a need to study the failure mode of advanced high-strength-steel spot welds. This paper aims at investigating the transition from the interfacial to the pullout failure mode during various loading conditions including the tensile-shear test, cross-tension and coach-peel tests of DP780 spot welds. It was found that there is a critical fusion-zone (FZ) size ensuring the pullout failure mode in each loading condition. The results showed that the critical fusion size increased in the following order: cross-tension, coach-peel and tensile-shear test. The behaviour of the transition from the interfacial to the pullout failure mode was explained in terms of the stress state of the weld for each loading mode.
Keywords: resistance spot welding; uporovno točkasto varjenje; način porušitve; failure mode; high-strength-steel; visokotrdnostno jeklo; loading condition; način obremenitve